Earning Per Share Sebagai Penentu: Studi Moderasi terhadap Hubungan Rasio Keuangan dan Harga Saham - I Gusti Agung Arista Pradnyani; Ni Luh Putu Widhiastuti (Universitas Muhammadiyah Palembang, 2025)
Purpose– This study aims to analyze the role of Earning Per Share (EPS) in moderating the effect of profitability and leverage on stock prices in property and real estate sector companies. This study is expected to enrich academic studies in finance and provide a deeper understanding for companies regarding the importance of EPS as a financial performance indicator that strengthens or weakens the relationship between financial ratios and stock values. Design/methodology– This study uses a quantitative approach with an associative design, which was conducted on 40 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Secondary data was obtained through documentation from the official IDX website, with a total of 80 observations. Data analysis was carried out using multiple linear regression through Moderated Regression Analysis (MRA), with the help of SPSS software version 26. Findings - The results of the study show that profitability has a positive effect on stock prices, while leverage has a negative effect. EPS is proven to act as a moderating variable that influences the relationship between profitability and leverage on stock prices. These findings provide theoretical contributions and recommend the addition of other variables, such as liquidity, dividend policy, and firm size, in further research to obtain a more comprehensive understanding of stock price determinants.